ENVIRONMENTAL PROBLEMS, RECYCLING, AND CLIMATE CHANGE THESIS STATEMENT - Raxmatjonov Muhammadaziz; To’raxon Abduraxmonov (TADQIQOTLAR, 2025)
Annotation:This paper examines the escalating severity of global environmental problems—most critically climate change—driven primarily by anthropogenic greenhouse gas emissions. It explains the interconnected challenges of resource depletion, pollution, and biodiversity loss, while emphasizing the centrality of climate change as a planetary crisis. The study evaluates the role of recycling and the circular economy as essential but insufficient responses within a broader sustainability framework. Through analysis of contemporary scientific assessments and international reports, including those of the IPCC, UNEP, OECD, and the Ellen MacArthur Foundation, the paper argues that recycling and resource-loop systems can significantly reduce environmental pressure but cannot independently resolve the climate crisis. The conclusion stresses that meaningful progress requires an urgent global transition to renewable energy, strong governance, systemic economic reform, and a collective societal shift toward sustainable consumption. Only a coordinated, holistic strategy can prevent irreversible ecological and socioeconomic consequences for humanity.